OPTIMIZATION OF YOGURT FERMENTED MILK PRODUCTS WITH THE ADDITION OF NATURAL STABILIZER BASED ON LOCAL POTENTIAL OF TARO STARCH (COLOCASIA ESCULENTA) - Aju Tjatur Nugroho Krisnaningsih; Dyah Lestari Yulianti; Imam Thohari; Puguh Surjowardojo (UNEJ e-Proceeding, 2016)
The aims of research were to improve the quality of the final product through the use of yogurt stabilizer based on local potential, easily obtainable stock and has a low price, namely taro starch (Colocasia esculenta). The method of research was laboratory experiment arranged in completely randomized design factorial. The first factor is the level of taro starch with 4 treatments (0%, 1%, 2%, 3%). The second factor is the concentration of starter with 3 treatments (1%, 3%, 5%). Each treatment was repeated 3 times. The variables measured and analyzed: 1) pH, 2) the acidity, 3) viscosity. The data were analyzed by Anova. If significant the Duncan’s Multiple Range Test was applied.The results showed the addition of stabilizer level provides a significant influence on the pH, acidity and viscosity of yogurt (P <0.01) but concentration starter not significant of pH and viscosity (P> 0.05) but very real effect on the acidity of the yogurt (P <0.01). Interaction taro starch level and inoculation starter does not give effect to the quality of the yogurt based on physico-chemical properties. pH yogurt with the addition of stabilizer level of 1%, 2% and 3% produce ideal pH after fermentation for ready consumption of 3.9. The acidity of the yogurt without stabilizer (0%) was 1,52% -2.02%. Addition of stabilizers 1% and above decreased the acidity of the yogurt. Level 3% of stabilizer provides the highest viscosity value of 27620 cP yogurt. While the lowest viscosity of the yogurt without addition of stabilizer (0%) of 840 Cp. Conclusions of research that the stabilizer taro starch level of 1% contribute to produce optimal quality yogurt products.